Analysis of costs and scarce fuel savings associated with nine Eastern and North Central center city conversions to a district energy system - Davis, A. A.; Santini, D. J.; Marder, S. M.; Bernow, S. S. (Argonne National Laboratory, 1979)
This study considers the major urbanized areas of nine US cities to arrive at rough estimates of costs required to retrofit them with district energy systems (DES). Only those costs associated with heating and hot water are addressed here. Demand estimates and energy-supply analyses are made, and component capital costs are estimated to arrive at annualized system costs. Finally, a comparison of alternative energy-delivery options is made, and estimates of scarce-fuel savings are derived. 49 references, 20 figures, 14 tables.